Augmented reality application on the tourism orientation sign digital system at the 'Bawah Langit' museum - Zuhriyah, Sitti; William Asrul, Billy Eden; Jura, Suwatri (ILKOM Jurnal Ilmiah, 2021)
One of the most visited tourism icons in Makassar is the Losari Beach Pavilion which provides many choices ranging from beautiful sunsets, typical banana epe cuisine, floating mosques, and rows of statues of heroes and icons of Makassar City which are spread over four platforms, namely Makassar Pavilion, Bugis Pavilion, Mandar and Toraja which is commonly called the Museum Under the Sky. In supporting the attraction, it is necessary to be equipped with an accurate explanation of the statues in the attraction. In the new normal that limits interaction with other people, digital and virtual explanations will be one solution to provide attractive and up-to-date information. This study aims to create a Digital Tourism Orientation Sign System, which is an information system that provides accurate explanations and descriptions of the hero statues in the Underground Sky Museum. With this application, the Losari Pavilion is one of the futuristic tourist attractions with local wisdom. This application has been tested using Alpha testing which includes distance testing with test results a minimum distance of 10 cm and a maximum distance of 1 m marker will be detected; light testing with object test results will appear from a room brightness level greater than 10 Lux.